Motivation and Life Satisfaction of Employees in the Public and Private Sectors - Julija Peklar; Eva Boštjančič (Central European Public Administration Review)
Work motivation is the steering of human activity towards a desired objective by means of motives generated internally in a person or in his or her environment, on the basis of his or her needs. The aim of this research was to verify whether the different types of work motivation employees reported in their work were influenced by sector, job, gender and education, and to assess how the different types of motivation are linked to life satisfaction. The research involved the participation of 288 employees – 153 in the private sector and 116 in the public sector (19 did not specify). The results show that among all employees the most distinctly expressed factor is intrinsic motivation. No differences in any type of motivation were observed between sectors; between managers in the public and private sectors there were no statistically significant differences in either extrinsic motivation or intrinsic motivation or in life satisfaction.